Linkages between Population Census and Demographic Statistics Data: Methodological Approaches and Research Opportunities - Jasilionis, Domantas; Stankūnienė, Vlada; Ambrozaitienė, Dalia; Trofimova, Olga (Lithuanian Journal of Statistics, 2014)
Unfavorable general demographic indicators are to a large extent predetermined by a demographic situation in some population groups. Therefore, in order to achieve a more sustainable demographic development at the country level and develop an adequate response from relevant population policies, it is necessary to measure the scale of demographic differentiation and identify population groups at risk. This requires reliable population-level data and innovative methods for measuring demographic differentials. The main aim of this work is to present advantages and capabilities of methodology for development of census-linked databases based on the linkages between census and demographic records. This study provides selected empirical examples and new scientific data on socio-economic and socio-demographic differences in mortality, first divorces, and births in Lithuania. These data can be further used for improving population policies in Lithuania and performing comparative analyses with other countries.